EKSTRAKSI POLISAKARIDA MANAN DARI BUNGKIL INTI SAWIT - Ihsan, Fikratul; Azzahro, Hanifah Ulfa; Anggraini, Anna; alhaviz, Alhaviz (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2024)
Palm kernel cake (PKE) is a residue product of palm kernel oil whose production has increased every year. Dietary fiber in there is mannan polysaccharides in palm kernel cake. Mannan polysaccharides consist of linear mannan, glucomannan, galactomannan and glucogalactomannan have the ability to bind water, so they can be used as thickeners by the food industry. This study aims to obtain the yield of mannan polysaccharides extracted using water solvent and NaOH solvents. The design used was a Completely Randomized Design (CRD) with one factor such as temperature (60oC, 100oC and 121oC) for water solvents and NaOH concentration (6%, 12% and 18%) for NaOH solvents. The results showed that temperature treatment had a significant effect on the yield produced and NaOH concentration treatment had a significant effect on the yield produced. The temperature treatment of 121oC produced the highest yield of 0.056 g/25 g BIS and the concentration treatment of 18% NaOH produced the highest yield of 0.281 g/25 mg BIS. The FTIR spectrum shows that the extraction results have increased the number of vibrations at a wavelength of 800-900 cm-1 which is the C-H vibration region (β-pyranose bond) as a characteristic band of mannan polysaccharides. Keywords: Palm kernel cake, NaOH, mannan polyssaccharides, temperature